Paul and identity construction in early Christianity and the Roman Empire - Mbwangi, F. Manjewa (HTS teologiese studies, 2020)
The question of what subjects Paul addresses in his letters has been a matter of debate in New Testament scholarship. This debate shows the evolution of Pauline studies, whereby early scholars argued that Paul addressed topics ranging from questions of human existence, to relations between Jews and Gentiles, and even topics connecting Paul with the Roman Empire. Most of these scholars view Paul mainly from a religious perspective, particularly in terms of the relationship between Judaism and Christianity. However, viewing Paul from a Jewish versus a Christian religious perspective only fails to present the multivalent function of the Pauline corpus. This article employs social identity theory to read Galatians 3:1–10 in order to defend the argument that Paul employs his letters to construct a superordinate identity for his community which embraces not only political perspectives but also has religious and economic trajectories.Contribution: The application of identification, contest and comparison, concepts derived from sociology, to analyze Galatians 3:1-10 in reference to 1st century economic, religious and political contexts to explain the multivalent nature of early Christian identity, contributes to multidisciplinary research aspects of Biblical studies which is in tandem with the scope of HTS Theological Journal.